Leg ulcer with long‐term hydroxyurea use. Issue 4 (24th February 2021) - Ammad Ud Din, Mohammad; Hussain, Syed Ather; Jamshed, Saad
Abstract: Long‐term use of hydroxyurea can cause leg ulcers which usually do not heal unless the drug is discontinued. Patients should be counseled regarding alternative lines of treatment like anagrelide and pegylated‐interferon. Abstract : Long‐term use of hydroxyurea can cause leg ulcers which usually do not heal unless the drug is discontinued. Patients should be counseled regarding alternative lines of treatment like anagrelide and pegylated‐interferon.